Transitional Morphology in Hybrids of Hirudo verbana and H. orientalis (Clitellata, Hirudinida) - Kovalenko, M.V.; Utevsky, S.Yu. (Вестник зоологии, 2013)
The aim of this research was to test the ability of hybridizing Hirudo orientalis S. Utevsky et Trontelj, 2005 and Hirudo verbana Carena, 1820. We obtained offspring from both species. The color pattern of all the hybrids was uniform and quite different from both the parents. The venter was similar to H. verbana. The dorsum was very similar to the color pattern of Hirudo medicinalis Linnaeus, 1758 that was not involved to the experiment. The coloration pattern of the hybrids, which is very similar to that of H. medicinalis suggests the hybrid origin of this species.